Varya's Individual Confrontation with Grief and Mortality in Chloe Benjamin's The Immortalists - Irfansyah, M. Ardy Noor; Marsih, Linusia (Cultural Narratives, 2025)
Death and grief, while universally experienced, manifest in profoundly different ways across individuals, shaped by personal history, psychological makeup, and existential circumstance. Literature has long served as a powerful medium for examining these individual differences in confronting mortality, offering readers an intimate lens into the diverse human responses to loss. Through this study, titled " Varya's Individual Confrontation with Grief and Mortality in Chloe Benjamin's The Immortalists," examines Varya who is the only one left among her siblings, a minority within her own family. “Burden” captures the inequality she faces in the face of death compared to her siblings. Using the framework of character and characterization, and the five stages of grief proposed by Elisabeth Kübler-Ross, denial, anger, bargaining, depression, and acceptance. This descriptive qualitative research highlights Varya’s transformation from an innocent eldest sister to someone cautious about death. Initially, Varya denies the prophecy predicting her death, followed by anger and frustration. Her pursuit of science serves as a form of bargaining, seeking to extend her life and assert control over her fate. As she confronts these challenges, she ultimately reaches acceptance, finding meaning in her relationships, particularly with her son, Luke. This study addresses that gap by examining how Varya's grief reflects both the universal dimensions of loss and the deeply personal differences that distinguish individual experiences of mortality. The study offers literary representations of grief by demonstrating that individual differences in confronting mortality are not signs of psychological fragility but rather dimensions of human resilience, empathy, and the enduring pursuit of a meaningful life.